Impact of Number of Exposed Carious Lesions as Reason for Pain or Tooth Extraction on Quality of Life of Children Aged 7-16 Years Attending Tertiary Care Hospitals in Peshawar - Ihtesham-Ud-Din, Ariffullah Khan, Ayesha Iftikhar, Muhammad Yousaf, Owais Naeem Khan, Hina Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Carious lesions are the record frequent oral health problem among school going kids everywhere the world. In the deciduous teeth, dental caries is the tenth most communal oral problem that affects about nine percent of the population worldwide. Aim: To report impact on quality of life of exposed carious lesion as reason for tooth extraction in 7-16 years children. Study design: Descriptive cross-sectional study. Place and duration of study: Sardar Begum Dental College and Peshawar Dental College, Peshawar from 1st January 2021 to 31st December 2021. Methodology: Three hundred and eight children aged 7-16 years of both genders were enrolled from two dental teaching hospitals of Peshawar. Children were examined clinically at a dental chair. A radiograph advised by the clinician was used to diagnose number of teeth having exposed carious lesions that are causing pain or extracted/filled because of pain were recorded for each participant in a structured data collection sheet. Child oral health impact short form was used to record oral health related quality of children. Results: There were 182(59.1%) males and 126(40.9%) females and mean age was 10.0±2.8 years. The correlation between OHRQoL and number of teeth with exposed carious lesions that are causing pain, filled or have been extracted because of pain is 0.610, which indicates positive correlation, as lesion increases the QoL of an individual will decrease. Conclusion: The positive correlations between OHRQoL and number of teeth having had exposed carious lesions that are causing pain, filled or have been extracted because of pain. It also signifies the negative impact of exposed carious lesion, over oral health related quality of life of 7-16 years old, visiting two tertiary care hospitals of Peshawar. Key words: Quality of life (QoL), Oral health related quality of life (OHRQoL), Peshawar